Bromodomain Protein BRD4 Is Essential for Hair Cell Function and Survival - Kannan-Sundhari, Abhiraami; Abad, Clemer; Maloof, Marie E.; Ayad, Nagi G.; Young, Juan I.; Liu, Xue Zhong; Walz, Katherina (Frontiers in Cell and Developmental Biology, 2020)
Hair cells (HCs) play crucial roles in perceiving sound, acceleration, and fluid motion. The tonotopic architecture of the sensory epithelium recognizes mechanical stimuli and convert them into electrical signals. The expression and regulation of the genes in the inner ear is very important to keep the sensory organ functional. Our study is the first to investigate the role of the epigenetic reader Brd4 in the mouse inner ear. We demonstrate that HC specific deletion of Brd4 in vivo in the mouse inner ear is sufficient to cause profound hearing loss (HL), degeneration of stereocilia, nerve fibers, and HC loss postnatally in mouse; suggesting an important role in hearing function and maintenance.